Novel Bidentate Amine Ligand and the Interplay between Pd(II) and Pt(II) Coordination and Biological Activity - Oliveira, Laiane S.; Rosa, Letícia B.; Affonso, Daniele D.; Santos, Igor A.; Da Silva, Jennyfer C.; Rodrigues, Gustavo C.; Harris, Mark; Jardim, Ana Carolina G. [UNESP]; Nakahata, Douglas H.; Sabino, José R.; de Carvalho, João E.; Miguel, Danilo C.; et al. (Wiley, 2024)
Pt(II) and Pd(II) coordinating N-donor ligands have been extensively studied as anticancer agents after the success of cisplatin. In this work, a novel bidentate N-donor ligand, the N-[[4-(phenylmethoxy)phenyl]methyl]-2-pyridinemethanamine, was designed to explore the antiparasitic, antiviral and antitumor activity of its Pt(II) and Pd(II) complexes. Chemical and spectroscopic characterization confirm the formation of [MLCl2] complexes, where M=Pt(II) and Pd(II). Single crystal X-ray diffraction confirmed a square-planar geometry for the Pd(II) complex. Spectroscopic characterization of the Pt(II) complex suggests a similar structure. 1H NMR, 195Pt NMR and HR-ESI-MS(+) analysis of DMSO solution of complexes indicated that both compounds exchange the chloride trans to the pyridine for a solvent molecule with different reaction rates. The ligand and the two complexes were tested for in vitro antitumoral, antileishmanial, and antiviral activity. The Pt(II) complex resulted in a GI50 of 10.5 μM against the NCI/ADR-RES (multidrug-resistant ovarian carcinoma) cell line. The ligand and the Pd(II) complex showed good anti-SARS-CoV-2 activity with around 65 % reduction in viral replication at a concentration of 50 μM.
Keywords: antioxidant; cancer; Palladium; Platinum; SARS-CoV-2